(untitled) (The International Journal of Educational Sciences and Arts, 2024)
When the disagreement occurred among the Fiqh schools in methodology and deduction, particularly between the school of Ahl Al-Hadith and the school of Ahl Al-Ra’y, it was important to examine and extrapolate the approach of each school in order to identify the points of agreement and disagreement between them. This research aims to identify Ahl Al-Hadith and the concept of Ahl Al-Hadith’s school, clarify the meaning of Ahl Al-Ra’y and the concept of Ahl Al-Ra’y’s school, deduce the methodology that each school adhered to and elucidate their contributions to the Sunnah and its sciences, and conduct a comparison between the two schools to highlight the points of agreement and disagreement between them. To this regard, I combine the inductive, analytical, and comparative approaches. Top of Form The research is arranged into an introduction, three treatises, a conclusion, a list of bibliography and references. Then the research ends with several findings, including: Ahl Al-Hadith refers to those who have a close connection with the traditions (Athar) through seeking, collecting, understanding, memorizing, narrating, following, and acting accordingly, both outwardly and inwardly, and they possess the critical faculty and the fine discernment to distinguish between authentic and unauthentic narrations of the Prophet (PBUH). Meanwhile, Ahl Al-Ra’y refers to those who consider issues and engage in Ijtihad (Shariah-based-reasoning), and use analogical deduction (Qiyas) in matters of creed and Fiqh, whether their Ijtihad is reprehensible or praiseworthy. As for the recommendations, the most significant among them is the need to understand that disagreement among the four schools of Fiqh pertains to subsidiary matters, while they agree on the fundamental principles of issues.